THE ROLE OF KINSHIP RELATIONS IN THE LIFE OF SURKHAN OASIS RESIDENTS - Rustamovich, Buriyev Ravshan (PT. Antis International Publisher, 2024)
In this article, the relatives of the residents of the Surkhan oasis and the related values are analyzed ethnographically.